Proposta de planejamento e controle da produção na agroindústria de moagem de trigo - Oliveira, Maico Jeferson de (2007)
This research approaches planning studies and production control in the Agribusiness of grain milling. With base on studies, one molding of planning system and production control is proposed. The planning molding system and production control was elaborated based on a bibliographic research and with data collection through questionnaires and the formulae. The data were colleted in the mills from South of Brazil. The supply to agribusiness of grain milling is characterized by instability and dependence of raw material supply coming from Argentina. The divergence between quality of national grain and the necessity of the industry is a part of Brazilian reality. The mills present typically by the times of receiving, preparation, milling of grains, packaging and shipping of flours. The flux of operations is the flow shop kind, where milling represents the restriction of the system. In the population studied, the millings present an inactive capacity related to Market Demand. It was developed a methodology of production control on the factory floor, based on productive and lost of rhythm from milling. The goal is to monitor the flux of production. The methodology was simulated in one of the mills from the sample. A proposal of master production planning to agribusiness of grain milling was elaborated. The data collection revealed the demand of this tool for planning and production control. The proposal was based on a complete programming of milling, where the sequence of production is accomplished based on the delivery date. The proposal even sees the frozen time that happens in the last period to guarantee the stability of the master production planning. The focus on raw material, that restricts resource in a long period represented by milling and the necessity of grouping of flour are the premises to elaborate an aggregate planning of production to agribusiness of grain milling.